ANALISIS PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP PEMBENTUKAN KOMITE MANAJEMEN RISIKO (Studi Empiris pada Perusahaan Finansial Non Perbankan yang Terdaftar di BEI Tahun 2009-2011) - Fatah Sambera, Gea; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2013)
The aim of this research is to examine the impact of board of commissioner characteristics and firm characteristics to the establishment of Risk Management Committee (RMC) in financial non bank firms. Establishment of Risk Management Committee in question is the existence of RMC in the company, whether affiliated with audit committee or separated from the audit committee and independent. Board of commissioner characteristics used in this research are proportion of independent commissioner, board size, and frequency of meetings. While the firm characteristics used in this research are financial reporting risk, leverage and business complexity, and firm size as control variable. Sample of this research were financial non bank firms listed in Indonesia Stock Exchange for the observation period from 2009 until 2011. Collecting data in this research used a purposive sampling method and resulted 57 samples. This research used logistic regression to analyze data. Result of this research showed that financial reporting risk affected positively and significant to the establishment both of affiliated RMC and Separated RMC and business complexity affected positively and significant to the establishment of affiliated RMC. While firm size as control variable had positive and significant impact to the establishment of affiliated RMC and Separated RMC.